2023
DOI: 10.3390/ijerph20043070
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with Family Planning amongst Persons with Mental Health Problems: A Nationwide Patient Survey

Abstract: High rates of unintended pregnancies in patients with mental health problems reflect the unmet need for tailored family planning. This study aims to explore aspects of family planning that are especially challenging for patients experiencing health problems by obtaining the perspective of (former) patients and those with close relationships with the (former) patients. In August 2021, members of a Dutch national mental health panel, consisting of (former) patients and close ones, were invited to respond to a 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Seventeen volunteers of the Dutch mental health umbrella organization MIND with self-reported psychiatric disorders were included. Participants were recruited from a sample of survey respondents ( n = 378) from MIND [ 5 ]. The survey was conducted to collect quantitative and qualitative information about family planning.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen volunteers of the Dutch mental health umbrella organization MIND with self-reported psychiatric disorders were included. Participants were recruited from a sample of survey respondents ( n = 378) from MIND [ 5 ]. The survey was conducted to collect quantitative and qualitative information about family planning.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies revealed that women with psychiatric disorders more often experience unintended pregnancies compared to counterparts without such vulnerability [ 1 3 ]. Moreover, childlessness is associated with having chronic illnesses, among which are psychiatric illnesses [ 4 , 5 ]. However, there is limited knowledge about contributing factors that shape family planning decision-making in women with psychiatric disorders [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation